In assenza di gravità Turismo, erotismo e cultura locale a Ischia nel secondo dopoguerra - Ugo Vuoso (EtnoAntropologia, 2018)
The arrival of the poet W.H. Auden and his partner C. Kallman at Forio, in Ischia island, at the end of 1940s, is considered as the beginning of the cultured, homophilic and unprejudiced period that persisted through the 1960s, the era when the largest island of the Campanian Archipelago became the site of a massive and pervasive mass tourism. Foreign artists and intellectuals established on the island, who were protagonists of erotic practices considered reprehensible, gave birth to a complex social phenomenon in which the locals, by elaborating an appropriate cultural background, played an ambiguous role in the relationship with the guests and the transformation of the local society.